Avaliação de vazões máximas estimadas a partir dos modelos HEC-HMS e SWMM : estudo de caso para o núcleo urbano e região periurbana de Muniz Freire - Souza, Tainah Christina Teixeira de (2017)
The determination of the project flow is a fundamental step for the correct design of drainage works or to enable the adequate decision making about non-structural actions related to Rainwater drainage. In areas that do not have fluviometric data are usually used the rainfall-flow models for indirect determination of the project flow. Function of the diversity of vailable models, it is up to the modeler to choose the model most appropriate to the singularities of the evaluated area. In this study, a comparative analysis of the Storm Water Management Model (SWMM) and Hydrologic Engineering Center (HEC-HMS) models was performed models about estimating the maximum flows associated associated with the urban area and periurban regions of Muniz Freire city, Espírito Santo. The estimation of the surface runoff was performed through the Unitary Hydrograph method and the losses of infiltration by the Chow-Gumbel method and the design rain by the alternating blocks method. The models presented relevant differences in the values of peak flow and volume of runoff. For recurrence periods between 2 and 5 years, the peak flow values and runoff volumes estimated by the SWMM were higher than those obtained by the HEC-HMS for all the basins evaluated, reversing this trend with the increase of the period of return. The simulations associated with the 10 and 20 year recurrence periods, usually used in urban drainage studies and projects, were the ones that presented the closest, with the lowest relative differences for the hydrological variables evaluated.